Building A Sub-Website: Facilitating Accessibility For Inclusive Higher Education Disability-Friendly Universities In Indonesia - Arifputri, Aiza Nabilla; Ekaputri, Sarah Derma; Gracia, Amanda Bunga; Lestari, Martha Tri; Aziz, Rifqi Abdul; Dhamayanti, Elfryda Amelia; Putra, Nandita Alya; Mahaputra, Komang Sadhu; Calista, Malika (Universitas Prof. Dr. Moestopo (Beragama), 2025)
The Community Service Program (CSM) aims to facilitate information access for students with disabilities aspiring to pursue higher education. In collaboration with internal partners from PUTI and international partners from Lancaster University, the program is developing a sub-website within Telkom University's platform as a Data Integration Hub for disability-friendly universities across Indonesia. This sub-website will serve as a central access point for comprehensive information on universities that support the needs of students with disabilities nationwide. Additionally, it will act as a research hub for disability inclusion studies. By updating the main website https://telkomuniversity.ac.id and introducing a sub-domain, the initiative seeks to make it easier for students with disabilities and their parents/guardians to access information about disability-friendly universities in Indonesia, both public and private. Currently, the working version of the website is hosted on the domain https://ideahub-snowy.vercel.app, pending security approval from the internal PUTI (Information Technology Centre). Disability-friendly universities are institutions that accommodate students with various types of disabilities across their faculties and programs nationwide. Through this development, the program aims to provide more accessible and inclusive information for individuals with disabilities, while also raising awareness about the importance of disability inclusion in educational environments.